An estimate of the possible impact of lower electricity and water tariffs on the Maltese economy - Aaron G. Grech (Central Bank of Malta, 2014)
This paper presents estimates of the possible impact on the Maltese economy of the reduction in electricity and water tariffs to residential customers that took place on 31 March 2014 and the subsequent lowering of tariffs to commercial customers, which is expected to take place in March 2015. These estimates are calculated using the structural macro-econometric model described in Grech et al (2013).
Keywords: C3; C5; E1; E2; 330